Massager-stimulator in clinical practice: scientometric analysis of evidence-based studies - G. N. Ponomarenko (Лечащий Врач)
Background. Scientific substantiation of effective methods of correction of diseases of the peripheral nervous system and musculoskeletal system is one of the promising areas of development of modern physical and rehabilitation medicine. The most effective methods of treating pathological scars are technologies of combined effects of hardware roller massage with spinal stretching due to the use of the patient's own body weight (autorecline of the spine) and electrostimulation of skeletal muscles causes pronounced synergistic therapeutic effects.Objective. To analyze evidence-based studies of high methodological quality on the use of technologies for the combined effects of hardware roller massage with spinal autorecline and electrical stimulation of skeletal muscles in patients with various diseases.Results. The analyzed sources of scientific evidence of the effectiveness of combined exposure technologies were dominated by studies performed on samples of patients with dorsopathy, osteochondrosis of the spine, herniated disc. The considered technologies cause significant clinical effects, manifesting pronounced relief of pain syndrome and remodeling of connective tissue.Conclusion. Evidence-based scientific databases contain a significant pool of information on high-quality clinical studies of the therapeutic effects of combined exposure to hardware roller massage with spinal autoreclination and electrostimulation of skeletal muscles in patients with vertebroneurological profile.